John Edgar Wideman, lecteur-archiviste de Frantz Fanon - Flora Valadié (Sillages Critiques)
This article intends to read Fanon, a Novel, written in 2008 by John Edgar Wideman, as an attempt to decolonize the archive, more specifically the Fanonian archive. Rather than trying to exhume the legacy of the Martiniquan thinker, the novel proposes to set Fanon’s thought in motion, allowing it to unfold before the reader’s eyes. Thus summoned up, the archive assumes an eminently political role. No longer an origin in a teleological narrative, it can only be apprehended by a text that deliberately practices generic blurring and intermingling as a mode of writing. In Fanon, a Novel, the intersection between fiction and the archive serves as a productive space where national and colonial grand narratives are defeated.